ANALYSIS OF STUDENTS’PRIORITY MOTIVESIN THE INDUSTRY OF ACTIVE TOURISM - Ячнюк, Максим; Ібрагімов, Еміль; Чубатенко, Севіль (My University, 2019)
Встановлено, що мотивацій до занять туризмом є багато, але лише деякі з них вагомимиі та-кими,що можуть впливати на результат прийняття рішення. Щоб з’ясувати мотивацію студентів у сфері туризму та відпочинку, необхідно встановити мотиви, якими молодь керується у своїх діях. Процес дослідження вимагав використання системного аналізу, соціологічних, педагогічних і мате-матичних методів. Опитування дало нам змогу встановити як молодь проводить своєдозвілля; виявитифактори, які змушують студентів бути активними; встановитипричини, які змушують студентів зайнятися обраною рекреаційною діяльністю; а також причини, що їм заважають та очікуваний ефект від такої діяльності.Проведене анкетування засвідчило, що студенти бажають активно від-почивати, мають мотиваційне ціннісне ставлення до занять активним туризмом і рекреаційною діяльністю
Виявлення пріоритетних мотивів студентської молоді в галузі активного туризму
Any activity proceeds from biological needs formed in the process of human being’s interaction with the environment.The study of students’of higher educational establishments motivation to participation in programs of recreational activity is an essential condition to help develop effective steps for the rise of students’motion behavior, said steps be based on the principles of the priority of needs, motives and interests of individualsOne of the main factors of choice travel decision is motivation. It is found that there are a lot of tourist’s motivations, but only some of them are weighty and can influence the decision outcome. To find out the students motivation in tourism and recreation there must be installed the motives, which guide young people in their actions. Thestudy process has required the use of system analysis, sociological, pedagogical and mathematical statistics methods. The questioning aimed at establishment of how the youth spends its leisure time; disclosure of factors that make students be active in recreation; finding the reasons that make students be engaged in chosen recreation/health-improving activity, as well as of reasons that prevent them from said activity; and the effect expected by students from such activity. It is proved that the motivational sphere always consists of a number of motives, ideals and values, needs, motivations, goals, interests, etc. The conducted questionnaires of students shows that students want to relax actively, have motivational value attitude to employment tourism and recreational activities. The students’leisure time depends, on the one hand, on demographic factors and social-cultural environment, on the other –it is connected with the system of their values, needs and interests.
Keywords: молодь, мотивація, рекреаційна активність, активне дозвілля.; young people, motivations, recreational activity, active leisure.